ETNOBOTANI TANAMAN ANTIPIRETIK MASYARAKAT DUSUN MESU BOTO JATIROTO WONOGIRI JAWA TENGAH - Arum Suproborini; Mochamad Soeprijadi Djoko Laksana; Dwi Fitri Yudiantoro (Universitas PGRI Madiun, 2018)
Traditional medicine in Indonesia has been known to the public long before formal health services with modern medicine. Indonesia has many species of plants that have properties to cure various diseases and some other useful properties for human health. Antipyretic plants are plants that have the property as a febrifuge. The content of flavonoids in plants merit as a reliever fever (antipyretic). This study aims to determine the garden plants that can be utilized by the community as a febrifuge. (antipyretic). The research method used is survey method. The location of the observation and sampling of the plants was done by purposive random sampling technique by plot plot size 2x2 meter, 5x5 meter (adjust the location of the land). Based on research and observation, there are 8 species of antipyretic plants tumeric (Curcuma domestica), papaya (Carica papaya), dadap (Erythrina sp), hibiscus (Hibiscus rosasinensis), rambutan (Nephelium lappaceum), banana ( Musa paradisiaca), soursop (Annona muricata), and yam (Pachirrhyzus erosus) which can be utilized by the local community.